Patient factors predictive of failure following high tibial osteotomy - Ron Gilat; Sumit Patel; Derrick M. Knapik; Aghogho Evuarherhe, Jr; Eric Haunschild; Kevin Parvaresh; Jorge Chahla; Adam Yanke; Brian Cole (Elsevier, 2021)
Introduction: The influence of patient demographic factors in predicting the success and failure of HTO remains largely unknown. Objectives: To determine factors associated with success or failure after high tibial osteotomy (HTO) for unicompartmental knee pain with varus deformity at a minimum of 2-year follow-up. Methods: A prospectively collected HTO outcomes registry was queried for patients undergoing HTO. Demographic, preoperative, intraoperative, radiographic, and postoperative data were collected. Patient factors were analyzed for their association with HTO failure, which was defined as conversion to uni- or total knee arthroplasty. Results: Seventy-five patients were identified (n = 58 males; n = 17 females) with a mean age of 37.3 ± 8.7 years at surgery and average follow-up of 5.5 ± 3.8 years. Forty-eight percent (n = 36) of patients underwent reoperation, 28% (n = 21) underwent hardware removal, and 17% (n = 13) converted to arthroplasty. Increased body mass index (BMI) (> 30 kg/m2) (P = .025) and age > 45 years (P = .020) were associated with HTO failure, while performance of concomitant procedures decreased failure probabilities (P = .008). Conclusion: s: High tibial osteotomy is an effective procedure for symptomatic patients with varus deformity, associated with a significant improvement in PROs, a moderate complication rate, and a high survival rate. Reoperation rates remain common, while failure rates requiring conversion to arthroplasty necessitate HTO be performed in appropriately selected patients. Performance of concomitant joint preservation procedures at the time of HTO was protective against HTO failure, while greater patient age and BMI were associated with HTO failures. Level of Evidence: Level 4, Case series